Etmopterus lailae sp. nov., a new lanternshark (Squaliformes: Etmopteridae) from the Northwestern Hawaiian Islands - Ebert, David A.; Papastamatiou, Yannis P.; Kajiura, Stephen M.; Wetherbee, Bradley M. (Zootaxa, 2017)
A new species of lanternshark, Etmopterus lailae (Squaliformes: Etmopteridae), is described from the Northwestern Hawaiian Islands, in the central North Pacific Ocean. The new species resembles other members of the “Etmopterus lucifer” clade in having linear rows of dermal denticles, and most closely resembles E. lucifer from Japan. The new species occurs along insular slopes around seamounts at depths between 314–384 m. It can be distinguished from other members of the E. lucifer clade by a combination of characteristics, including a longer anterior flank marking branch, arrangement of dermal denticles on the ventral snout surface and body, flank and caudal markings, and meristic counts including number of spiral valve turns, and precaudal vertebrate. A key to species of the Etmopterus lucifer-clade is included.